Profil Kesiapan Calon Guru Fisika dalam Implementasi Pembelajaran Inquiry Berbasis Kompetensi Abad ke-21 - Mahir; Eka Ariaty B; Abdul Hakim; Farida Febriati (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Inquiry learning is an essential approach in 21st-century education because it develops students' critical thinking, problem-solving, and scientific literacy. However, limited pedagogical readiness among prospective physics teachers hinders effective inquiry implementation, making this investigation timely and necessary. This research analyzes prospective physics teachers' readiness to design and implement inquiry learning. A quantitative descriptive approach involved 14 physics education students enrolled in a microteaching course. Data were collected using observation sheets and learning-tool assessments, then analyzed descriptively based on inquiry learning indicators. Results revealed good readiness in organizing inquiry syntax and managing learning activities, although difficulties remained in developing investigative questions, facilitating scientific discussions, and conducting inquiry-based assessment. These findings highlight practical implications for strengthening inquiry experiences during microteaching while contributing theoretically to pedagogical readiness development. Furthermore, improved teacher preparation may enhance future classroom inquiry quality and student learning outcomes. Future research should involve larger samples, diverse institutions, and longitudinal designs to evaluate sustained readiness development and instructional effectiveness.